Properties of chitin extracted from Estonian mushrooms - Stephanie Baumgartner (Proceedings of the Estonian Academy of Sciences, 2019)
Fungi contain a significant amount of chitin in their cell walls presenting an attractive source for this commercially significant material. In this study, chitin was extracted from eight different mushroom species native to Estonia. Significant differences in molar mass, chitin content, and fibre size were observed while the degree of acetylation was mostly similar.